1995
DOI: 10.1007/bf02576782
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia reperfusion of the pancreas: A new in vivo model for acute pancreatitis in rats

Abstract: Based on the concept that ischemia is an important factor in the pathogenesis of acute pancreatitis, we developed a new model of complete ischemia/reperfusion of the pancreas in the rat. The aim of this study was to investigate the microcirculation of the pancreas after complete and reversible ischemia at different times after reperfusion by using intravital fluorescence microscopy. In addition, the effect of ischemia/reperfusion on the pancreas was assessed by means of light and electron microscopy and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 26 publications
3
58
0
1
Order By: Relevance
“…[9,10] In addition, microvascular perfusion failure is a characteristic hallmark of pancreatitis. [10][11][12] Since Panum [13] presented the first report, other researchers have reported that the pancreas is highly sensitive to ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…[9,10] In addition, microvascular perfusion failure is a characteristic hallmark of pancreatitis. [10][11][12] Since Panum [13] presented the first report, other researchers have reported that the pancreas is highly sensitive to ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…As described by Hoffmann et al [28], randomly selected non-overlapping regions of the exposed pancreatic tail were scanned at 1 h and 2 h after the onset of reperfusion. FCD, defined as the length of all red blood cell-perfused capillaries per observation area (centimetres per square centimetre), was determined by off-line analysis of ten randomly chosen exocrine observation areas (350 pmx200 pm) per time point, according to the method described by Schmid-Schoenbein et al [29].…”
Section: Assessment Of Microcirculationmentioning
confidence: 99%
“…The complication develops in 9 % of patients with haemorrhagic shock and 27 % of patients undergoing cardiac surgery with extracorporeal bypass [115], and to date this problem is unresolved in terms of aetiology and treatment [116]. Experimental studies show that acute pancreatitis is another problem that must be solved at the level of the microcirculation [117]. Analysis of the mechanism underlying the vasodilation that is inherent to the inflammatory effect, and the accompanying activation of leukocytes, shows that the kallikrein-kinin system is involved, particularly bradykinin.…”
Section: Surgery Reperfusion and Microcirculationmentioning
confidence: 99%